Sprawcy i sprawczynie Zagłady a podejście do sprawiedliwości w NRD w latach 1949–1963 - Lower, Wendy (Zagłada Żydów. Studia i Materiały, 2012)
Drawn from archives of the former German Democratic Republic (GDR), and mainly the files of the Ministry for State Security (Stasi) and regional court records, this essay analyzes two lesser-known trials of Nazi perpetrators of the Holocaust in wartime Galicia. One case features a typical German gendarme convicted but released from prison in the 1950s; the other features a married couple who shot Jews and others on an SS agricultural estate. Both cases highlight East German investigation methods and prosecutors’ use of evidence, while the second affords an opportunity to consider gendered aspects of wartime crimes and postwar trials. On the basis of these cases the author examines how evolving political considerations in the 1950s and 1960s shaped investigations, judicial process s, and sentences against Nazi perpetrators